Teacher's Pedagogic Competence In Evaluating Learning - Ayu Asri Milania; Wahyuni Murniati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to determine the teacher's ability to develop assessment tools according to learning objectives, carry out assessments with various techniques, and analyze the results of the assessment. The type of research used is descriptive qualitative. Data collection techniques used in this study are observation, interviews, and documentation. The data analysis technique used applies the concept of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of this study are: (1) The teacher has met the indicators in compiling an assessment tool that is in accordance with the learning objectives, namely establishing basic competencies and formulating activities, determining assessment techniques and criteria, determining the place and time for assessment. (2) The teacher has applied various PAUD assessment techniques in carrying out the assessment, namely observation, conversation, assignment, performance, and children's work. (3) The teacher has analyzed the results of the assessment to identify the achievement of children's development by first collecting the assessment data, then processing the data to observe the achievement of each child's development, then reporting the results of the assessment each semester to parents in the form of reports on the progress of students. Keyword : Competence, Teacher, Evaluation